Improved glycemic control of children and youth with type 1 diabetes in Iceland in 2008-2022 - Hansen, Jakob; Konradsdottir, Elisabet; Bjarnason, Ragnar; Jonsdottir, Berglind (Laeknabladid, 2025)
Introduction: Type 1 diabetes is characterized by destruction of the insulin-producing beta cells causing hyperglycemia. Insulin treatment targeting euglycemia mitigates complications. This study aims to assess glycemic control in Icelandic children with diabetes over the past 14 years and examine the impact of a semi-automatic insulin pump. Methods: The study included Icelandic pediatric patients with type 1 diabetes from the past 14 years. Data on HbA1c, date of diagnosis, co-occurring diagnoses, sex, age, number of ketoacidosis diagnoses, and the introduction of a semi-automatic insulin pump were gathered from medical records. Results: The average of means HbA1c peaked in 2012 at 70,4±11,3 mmol/mol and had its nadir in 2022 at 59,5±11,2 mmol/mol. The proportion of children with HbA1c over 70 mmol/mol was highest in 2011 (51.8%) and lowest in 2022 (10.2%). Females had higher HbA1c levels, the difference decreased by the end of the study period. Mean HbA1c decreased by 6.4 mmol/mol 18 months after introduction of a semi-automatic insulin pump. There was no significant change in mean HbA1c when 18 months prior and post introduction were compared. No change in incidence was observed over the period. Between 2018-2023, 11.2% had hypothyroidism, 2.2% had celiac disease, and 29 cases of ketoacidosis were diagnosed. Discussion: Significant progress has been made in treating Icelandic children with type 1 diabetes in recent years. There was no increase in incidence, contrary to other studies. The impact of the semi-automatic insulin pump was less pronounced than in other studies, possibly due to a longer follow-up period.